2019
DOI: 10.1128/mbio.00663-19
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants in the Glycerol Kinase Gene Reduce Tuberculosis Drug Efficacy

Abstract: Despite the administration of multiple drugs that are highly effective in vitro, tuberculosis (TB) treatment requires prolonged drug administration and is confounded by the emergence of drug-resistant strains. To understand the mechanisms that limit antibiotic efficacy, we performed a comprehensive genetic study to identify Mycobacterium tuberculosis genes that alter the rate of bacterial clearance in drug-treated mice. Several functionally distinct bacterial genes were found to alter bacterial clearance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
133
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(144 citation statements)
references
References 40 publications
10
133
1
Order By: Relevance
“…The genes identified are involved in a range of functions and include pathways known to alter antibiotic efficacy. For example, pncA and glpK mutants were found to be less sensitive to PZA treatment, consistent with previous studies (36). Conversely, we identified mutants in ppe50/51, which had previously been shown to increase the efficacy of a multidrug regimen (36).…”
Section: Selection Of Transposon Mutant Libraries In Antibiotic-treatsupporting
confidence: 91%
See 1 more Smart Citation
“…The genes identified are involved in a range of functions and include pathways known to alter antibiotic efficacy. For example, pncA and glpK mutants were found to be less sensitive to PZA treatment, consistent with previous studies (36). Conversely, we identified mutants in ppe50/51, which had previously been shown to increase the efficacy of a multidrug regimen (36).…”
Section: Selection Of Transposon Mutant Libraries In Antibiotic-treatsupporting
confidence: 91%
“…For example, pncA and glpK mutants were found to be less sensitive to PZA treatment, consistent with previous studies (36). Conversely, we identified mutants in ppe50/51, which had previously been shown to increase the efficacy of a multidrug regimen (36). We also identified multiple mutants lacking putative antibiotic efflux pumps, including ABC transporters Rv1747 and Rv1273, which were more susceptible to INH and RIF, respectively.…”
Section: Selection Of Transposon Mutant Libraries In Antibiotic-treatsupporting
confidence: 89%
“…GlpK is an enzyme required for glycerol catabolism via the lower glycolytic pathway and is essential for growth in media with glycerol as the sole carbon source ( Bellerose et al, 2019 ). A M. tuberculosis mutant missing this gene was recently found to be tolerant to several drugs when bacteria were grown on glycerol ( Bellerose et al, 2019 ).…”
Section: Glpk Phase Variation As a Rapidly Reversible Genetimentioning
confidence: 99%
“…GlpK is an enzyme required for glycerol catabolism via the lower glycolytic pathway and is essential for growth in media with glycerol as the sole carbon source ( Bellerose et al, 2019 ). A M. tuberculosis mutant missing this gene was recently found to be tolerant to several drugs when bacteria were grown on glycerol ( Bellerose et al, 2019 ). Interestingly, two independent groups recently showed that glpK is subjected to phase variation due to frequent and reversible frameshift mutations in a homopolymeric 7G sequence present at the 5' half of its open reading frame.…”
Section: Glpk Phase Variation As a Rapidly Reversible Genetimentioning
confidence: 99%
See 1 more Smart Citation